(3LRA ajg GdVYaGA hGdeJQhcjfs - (3GdOQGbWfj, GdTGaYj, CHh GdMSf, Ydj Hf YeQ Hf CMeO Hf egOj, J (B385 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B..(3bGd CHh HcQ CMeO Hf eMeO Hf ZGdH GdNhGQRej GdHQbGfj WGdJ eMGhQJj eY CHj efUhQ EHQGgje Hf GdMSjf GHf LecGf dCHj GdMSf Ydj Hf YeQ GdOGQbWfj YaG Gddg Yfj hYfgeG aj GdeJQhcjf ef CUMGH GdMOjK (B...s
(3BNQgG (B:s
.. (3GdChRGYj eKd fGaY hYWGA GdRgQj ajSbW CSeGA GdVYaGA hjLYdgG Yf GdChRGYj Yf YWGA eYfi eKd YHO Gddg Hf YGeQ GdCSdej hGSeGYjd Hf eSde (B. (3BNQ GdcJGHs
(3JHUQI GdYfhGf (B:s
(3WHY HJMbjb ehab YHO GdbGOQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B4\314s
(3agQSI GHf NjQ GdETHjdj (B178 ( 341)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs